长链非编码RNA PCGEM1通过转化生长因子β2/Smad2信号通路调控口腔鳞状细胞癌侵袭和转移的机制研究 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2020)
OBJECTIVE: To investigate the mechanism underlying the regulation of the invasion and metastasis of oral squamous cell carcinoma (OSCC) by long-chain noncoding RNA (lncRNA) PCGEM1 through the transforming growth factor (TGF) β2/Smad2 signaling pathways. METHODS: A total of 60 OSCC cases were collected. Cancer tissues and normal tissues more than 2 cm away from cancer tissues were also collected. Real-time quantitative polymerase chain reaction (qRT-PCR) was used to detect the expression of miR-148a and lncRNA PCGEM1 in OSCC, adjacent normal tissues, oral mucosa epithelial cells, KB, BcaCD885, SCC-4, CAL27, and SCC-15. The relationship between the expression of lncRNA PCGEM1 and miR-148a and the clinicopathological information of patients was analyzed. The lncRNA PCGEM1-silenced cell line KB-siPCGEM1 and negative control (KB-NC) group were constructed, and KB was used as the blank control group. The effects of lncRNA PCGEM1 on the proliferation, invasion, and migration of KB cells were determined via MTT, Transwell, and scratch assays. The bioinformatics website starBase was used to predict the complementary binding microRNA (miRNA) of lncRNA PCGEM1. Furthermore, the genes that the miRNA could target and bind were predicted in accordance with the website www.microRNA.org. Western blotting analysis was used to detect the expression of TGF β2/Smad2 signaling pathway proteins. RESULTS: qRT-PCR results showed that the expression level of lncRNA PCGEM1 and miR-148a in OSCC tissues was higher than that in normal tissues (P<0.05). The expression of lncRNA PCGEM1 and miR-148a in the cancer tissues of patients with different TNM grades, lymph node metastasis, and tissue differentiation was statistically significant (P<0.05). Compared with those in the blank control group and the KB-NC group, OD(492 nm) value was significantly decreased and cell mobility was significantly reduced in the KB-siPCGEM1 group (P<0.05). Bioinformatics predictions showed that lncRNA PCGEM1 could bind to miR-148a in a complementary manner and that miR-148a had a targeted binding site with TGF β2. qRT-PCR and Western blotting analysis results showed that the expression levels of miR-148a, TGF β2, and p-Smad2 in the KB-siPCGEM1 group were significantly lower than those in the blank control and KB-NC groups (P<0.05), and no statistically significant difference between the blank control group and the KB-NC group was observed (P>0.05). CONCLUSION: LncRNA PCGEM1 is highly expressed in OSCC. The high expression of lncRNA PCGEM1 may enhance the TGF β2/Smad2 signaling pathway by upregulating miR-148a, thus promoting the development of OSCC.